Co-doped titanium dioxide nanoparticles decrease the cytotoxicity of experimental hydrogen peroxide gels for in-office tooth bleaching - Kury, Matheus; de Oliveira Ribeiro, Rafael Antonio [UNESP]; de Souza Costa, Carlos Alberto [UNESP]; Florez, Fernando Luís Esteban; Cavalli, Vanessa (Springer Nature, 2024)
Objective: To evaluate the efficacy and cytotoxicity of experimental 6% and 35% hydrogen peroxide gels (HP6 or HP35) incorporated with titanium dioxide nanoparticles (NP) co-doped with nitrogen and fluorine and irradiated with a violet LED light (LT). Methods: Bovine enamel-dentin disks adapted to artificial pulp chambers were randomly assigned to bleaching (n = 8/group): NC (negative control), NP, HP6, HP6 + LT, HP6 + NP, HP6 + NP + LT, HP35, HP35 + LT, HP35 + NP, HP35 + NP + LT, and commercial HP35 (COM). Color (ΔE00) and whiteness index (ΔWID) changes were measured before and 14 days after bleaching. The extracts (culture medium + diffused gel components) collected after the first session were applied to odontoblast-like MDPC-23 cells, which were assessed concerning their viability, oxidative stress, and morphology. The amount of HP diffused through the disks was determined. Data were analyzed by generalized linear models or Kruskal Wallis Tests (α = 5%). Results: HP6 + NP + LT exhibited ΔE00 and ΔWID higher than HP6 (p < 0.05) and similar to all HP35 groups. HP6 + NP + LT showed the lowest HP diffusion, and the highest cell viability (%) among bleached groups, preserving cell morphology and number of living cells similar to NC and NP. HP6 + LT, HP6 + NP, and HP6 + NP + LT exhibited the lowest cell oxidative stress among bleached groups (p < 0.05). HP35, HP35 + LT, and HP35 (COM) displayed the lowest cell viability. Conclusion: HP6 achieved significantly higher color and whiteness index changes when incorporated with nanoparticles and light-irradiated and caused lower cytotoxicity than HP35 gels. The nanoparticles significantly increased cell viability and reduced the hydrogen peroxide diffusion and oxidative stress, regardless of HP concentration. Clinical Significance: Incorporation of co-doped titanium dioxide nanoparticles combined with violet irradiation within the HP6 gel could promote a higher perceivable and acceptable efficacy than HP6 alone, potentially reaching the optimal esthetic outcomes rendered by HP35. This approach also holds the promise of reducing cytotoxic damages and, consequently, tooth sensitivity.
Keywords: Hydrogen peroxide; Light irradiation; Nanoparticles; Tooth bleaching; Toxicity